2004
DOI: 10.1177/039139880402700614
|View full text |Cite
|
Sign up to set email alerts
|

Pulse High Volume Hemofiltration

Abstract: The correct surname is reprinted above, with apologies to the Author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Based on these studies and taking into account the disparate clinical results achieved in the past with high-volume hemofiltration [27][28][29][30][31] , the Vicenza group has proposed a novel convective approach for the management of septic shock termed pulse high-volume hemofiltration [32,33] . These investigators observed correctly that previous pharmaceutical interventions targeting a specific inflammatory mediator and administered at a discrete time point have largely failed because of the dynamic nature of the septic process [34,35] , the exception being activated protein C [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies and taking into account the disparate clinical results achieved in the past with high-volume hemofiltration [27][28][29][30][31] , the Vicenza group has proposed a novel convective approach for the management of septic shock termed pulse high-volume hemofiltration [32,33] . These investigators observed correctly that previous pharmaceutical interventions targeting a specific inflammatory mediator and administered at a discrete time point have largely failed because of the dynamic nature of the septic process [34,35] , the exception being activated protein C [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors recommend the use of the renal replacement therapy in rhabdomyolisis only if there is progressive raise in kalium levels, oliguria (<0.5 mL of urine per kilogram per hour for 12 hours), anuria, volume overload, or resistant metabolic acidosis-pH < 7.1 [7]. Common techniques of dialysis have shown a limited capacity for removal of circulating myoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous treatments with a dose greater than 45 ml/kg/h identify very high-volume hemofiltration (VHVHF) modalities. Intermittent procedures with brief, very high-volume treatments at 100 to 120 ml/kg/h for 4–8 h, followed by conventional CVVH, are identified as pulse HVHF [ 34 ]. However, there is no evidence that HVHF, when compared with standard dose hemofiltration, leads to a reduction in mortality [ 35 ].…”
Section: Extracorporeal Therapies and Treatmentsmentioning
confidence: 99%